If $a_n$ is a sequence of non-increasing positive numbers, then suppose we already know that $$\sum_p a_p$$ converges, when $p$ runs over the primes, what should be used to prove that $$\sum_n \frac{a_n}{\log{n}}$$ also converges, where $n$ runs over the positive naturals?

And also, how to show the converse is also true?

  • $\begingroup$ Do you mean that the first series is summed over all primes and the second series is summed over all positive integers? $\endgroup$
    – Bill Cook
    Oct 16, 2011 at 1:31
  • $\begingroup$ Sounds intuitively plausible, given the Prime Number Theorem. $\endgroup$ Oct 16, 2011 at 1:52
  • 1
    $\begingroup$ @robjohn: I call that strictly decreasing - see en.wikipedia.org/wiki/Monotonic_function $\endgroup$ Oct 16, 2011 at 10:50
  • 1
    $\begingroup$ @robjohn: You just said that monotone decreasing adopts a strict inequality. $\endgroup$ Oct 16, 2011 at 12:44
  • 1
    $\begingroup$ @AD: there are various usages. Just saying "decreasing" is usually ambiguous. Monotone decreasing is less ambiguous and usually means strictly decreasing, which is $a_{n+1}<a_n$. non-increasing definitely means $a_{n+1}\le a_n$. I have also seen monotone non-increasing also. $\endgroup$
    – robjohn
    Oct 16, 2011 at 13:22

3 Answers 3


I would use (1) $p_n \approx n\ln n$ and $p_{n+1} < (1+\epsilon)p_n$ for any $\epsilon$ for large enough $n$. This will allow you to handle the step from $a_{p_n}$ to $a_{p_{n+1}}$.


$$ \sum_n \frac{a_n}{\log n} \leq \sum_n \frac{a_{p_n}}{\log p_n}(p_{n+1}-p_n)$$

Now if you prove that the sequence $ \frac{p_{n+1}-p_n}{\log p_n}$ is bounded, you are done. I guess that this would be easy using the fact that $\frac{p_n}{n \log n} \to 1$ as $n \to \infty$.

  • 2
    $\begingroup$ I would be very interested in the easy proof of the boundedness of $\frac{p_{n+1}-p_n}{\log p_n}$. $\endgroup$
    – robjohn
    Oct 16, 2011 at 14:27
  • 2
    $\begingroup$ The gaps between primes are not O(log n). $\endgroup$
    – zyx
    Oct 17, 2011 at 4:09
  • $\begingroup$ Ok then. Sorry about that. I will delete the answer. $\endgroup$ Oct 17, 2011 at 5:57

Going back to the ratio test (http://en.wikipedia.org/wiki/Ratio_test), we have: $$\lim_{n\rightarrow \infty} \sup \frac{a_{p_{n+1}}}{a_{p_{n}}}=R$$ where $R \leq 1$ (it exists because $0 < \frac{a_{p_{n+1}}}{a_{p_{n}}} \leq 1 $, i.e. bounded).

If $R < 1$, then (1) $$\sum_{n}\frac{a_{n}}{\log n}=\sum_{n}\frac{a_{n}\cdot \pi(n)}{n}\cdot \frac{n}{\pi(n)\cdot \log n}< \left ( 1 + \varepsilon \right )\sum_{n}\frac{a_{n}\cdot \pi(n)}{n}$$ Now, assuming: $$p_{n}=n_{0}<n_{1}<...n_{k}<p_{n+1}$$ we have $$a_{p_{n}}\geq a_{n_{j}}, 0\leq j\leq k$$ $$n=\pi(p_{n})=\pi(n_{0})=\pi(n_{1})=...=\pi(n_{k})$$ and $$\frac{a_{p_{n}}\cdot \pi(p_{n})}{p_{n}} \geq \frac{a_{n_{j}}\cdot \pi(n_{j})}{n_{j}}$$ or (2) $$\left ( k+1 \right )\cdot \frac{a_{p_{n}}\cdot \pi(p_{n})}{p_{n}}\geq \sum_{j=0}^{k}\frac{a_{n_{j}}\cdot \pi(n_{j})}{n_{j}}$$ Considering that $k+1=p_{n+1}-p_{n}$ and $p_{n+1}-p_{n} < p_{n}$ (http://en.wikipedia.org/wiki/Bertrand's_postulate) $$a_{p_{n}}\cdot \pi(p_{n}) \geq \sum_{j=0}^{k}\frac{a_{n_{j}}\cdot \pi(n_{j})}{n_{j}}$$ Or ($\pi(p_{n})=n$): $$\sum_{n}\frac{a_{n}}{\log n} < \left ( 1 + \varepsilon \right ) \sum_{n}\frac{a_{n}\cdot \pi(n)}{n}\leq \left ( 1 + \varepsilon \right )\sum_{n}n\cdot a_{p_{n}}$$ Now $$\lim_{n\rightarrow \infty } \sup \frac{(n+1)\cdot a_{p_{n+1}}}{n\cdot a_{p_{n}}}=R< 1$$ It is also worth noting that for $\forall p_{k} \leq n$, $a_{p_{k}} \geq a_{n}$ and as a result: $$\sum_{k=1}^{\pi (n)}a_{p_{k}}\geq \pi (n)\cdot a_{n}$$ Or: $$\lim_{n\rightarrow \infty } \pi (n)\cdot a_{n} \leq \sum_{n}a_{p_{n}}< \infty $$ But if we assume $$\lim_{n\rightarrow \infty } \pi (n)\cdot a_{n}=\gamma >0$$ then from some $n$ we have $\pi (n)\cdot a_{n} > \frac{\gamma }{2}$ or $a_{n} > \frac{\gamma }{\pi (n)\cdot 2}$ or $a_{p_{n}} > \frac{\gamma }{n\cdot 2}$, this will contradict the convergence of the $\sum a_{p}$ and $\gamma =0$. So for $R < 1$ the statement seems to be true.

However for $R=1$, the original condition may not be sufficient. Let's assume $$\lim_{n\rightarrow \infty} \frac{a_{p_{n+1}}}{a_{p_{n}}}=1$$ strictly. Then, (1) becomes: $$\left ( 1 - \varepsilon \right )\sum_{n}\frac{a_{n}\cdot \pi(n)}{n} < \sum_{n}\frac{a_{n}}{log(n)}< \left ( 1 + \varepsilon \right )\sum_{n}\frac{a_{n}\cdot \pi(n)}{n}$$

And (2) becomes: $$\left ( p_{n+1} - p_{n} \right )\cdot \frac{a_{p_{n+1}}\cdot \pi(p_{n})}{p_{n+1}} \leq \sum_{j=0}^{k}\frac{a_{n_{j}}\cdot \pi(n_{j})}{n_{j}} \leq \left ( p_{n+1} - p_{n} \right )\cdot \frac{a_{p_{n}}\cdot \pi(p_{n})}{p_{n}}$$

And: $$\left ( p_{n+1} - p_{n} \right )\cdot \frac{a_{p_{n+1}}\cdot \pi(p_{n})}{p_{n+1}}=\left ( p_{n+1} - p_{n} \right )\cdot \frac{a_{p_{n}}\cdot \pi(p_{n})}{p_{n}} \cdot \frac{p_{n}}{p_{n+1}} \cdot \frac{a_{p_{n+1}}}{a_{p_{n}}}$$

This indicates (considering the assumption) that: $$\sum_{n}\frac{a_{n}}{\log n} < \infty \Leftrightarrow \sum_{n} \left ( p_{n+1} - p_{n} \right )\cdot \frac{a_{p_{n}}\cdot \pi(p_{n})}{p_{n}} < \infty \Leftrightarrow \sum_{n} \frac{p_{n+1} - p_{n}}{\log p_{n}} \cdot a_{p_{n}}< \infty$$

  • $\begingroup$ Unfortunately, the case $r=1$ is where most of the interesting behaviour lies. Also, you seem to be assuming a converse of the ratio test: the limit $r$ might not even exist (although the lim sup is certainly $\le 1$ in this case). $\endgroup$
    – Erick Wong
    Jan 28, 2013 at 0:56
  • $\begingroup$ I see, then switching to root test (en.wikipedia.org/wiki/Root_test) should work for the case when $r<1$, considering that $\lim_{n \to \infty }\sqrt[n]{n}=1$ $\endgroup$
    – rtybase
    Jan 28, 2013 at 9:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.